Assessment of the value of grasslands in Olszówka (Mszana Dolna Commune, Southern Poland) - Traczyk, Monika; Kucab, Anna (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2024)
The botanical composition of meadows and pastures and their value in use should determine the activities undertaken on grasslands in order to maximise their yields. The aim of the study was to analyse the floristic composition of meadows and pastures in the area of Olszówka village (Southern Poland), their characteristics and determination of the value in use and agricultural suitability. In the meadows and pastures, 50 plots, each with an area of 25 m2, were marked out and floristic lists were made on them according to the Klapp method. In the analysed area, the presence of five groups of similar plots was determined: I – pasture with Lolium perenne, II – meadow with Dactylis glomerata, III – meadow/pasture with Phleum pratense and Poa pratensis, IV – meadow with Arrhenatherum elatius, V – weeded meadow/pasture with Plantago lanceolata. Usage studies have shown that most of the plots have medium and good forage values. In order to improve the quality of meadows and pastures, undesirable species should be limited and appropriately selected care treatments should be intensified.